The vocational maturity of socio-economically stratified groups of high school senior students - Manalac, Asuncion Demetillo 1935- (s.n.], 1968)
The study determined the vocational maturity level of graduating high school seniors. The situational factors such as family socio-economic status and the influences operating in the students' vocational choices and decision-making behavior were explored. Findings revealed that the vocational interests of the students leaned strongly on scientific, professional and commercial fields rather than on the aesthetic, mechanical and agricultural/personal service. Highly vocationally mature students are found in greatest number within the middle group.